Genotypic discrimination of serovars belonging to the serogroup Icterohaemorrhagiae of Leptospira interrogans (Spirochaetales: Leptospiraceae) and the analysis of genetic distances using principal coordinates (FAVE Sección Ciencias Veterinarias, 2017)
Leptospirosis is the world`s most widely distributed zoonosis and of great importance in animal health and in public health.  The relevance of the serogroup Icterohaemorrhagiae relies on the frequent isolation from rodents and from clinical cases of humans, canines, bovines and swine; and this serogroup was also isolated from water samples of the Reconquista river, Buenos Aires province, Argentina. The objective of this study was to discriminate molecularly between serovars Copenhageni and Icterohaemorrhagiae being of importance in Argentina, using Multiple Locus Variable number tandem repeats analysis (MLVA) and analyzing the genetic distances among genotypes obtained from animal isolates in this study. We genotyped the four referential strains of the serogroup Icterohaemorrhagiae belonging to the species Leptospira interrogans serovar Copenhageni strain M20 and strain Ictero I  and of the serovar Copenhageni strain RGA and strain Fiocruz L1-130. In this study we included 24 strains isolated from animals domestic and wildlife. Using this technique we could determine numeric codes for each serovar and in this way, discriminate between serovars of this serogroup. The principal coordinates analysis (PCoA) showed the genetic variability of the four referential strains from the serogroup Icterohaemorrhagiae, the genotype with better representation was serovar Copenhageni strain Fiocruz L1-130 with 13 isolated strains with this genetic profile.  Discrimination of the serovars from this important serogroup allows to establish differences between clinical signs and/or response to treatment in the clinical cases produced by different serovars of the serogroup Icterohaemorrhagiae successfully distinguished in this study.
Keywords: Leptospira interrogans; Leptospirosis; Ichterohaemorrhagiae; molecular characterization